(untitled) (World Economics and Finance Bulletin, 2025)
This study investigates the role of strategic awareness in achieving strategic ambidexterity, aiming to establish a cohesive theoretical framework that addresses critical issues discussed by scholars and researchers in this field. It also provides an analytical perspective based on feedback collected from government bank employees in Maysan Governorate. Out of 156 employees, a sample size of 144 was selected for the study. The study utilized a questionnaire to gather data, followed by comprehensive statistical analyses conducted through multiple methodologies, facilitated by the Smart PLS software. The findings validated the study’s hypothesis, highlighting the influential interplay between its variables. Additionally, the study offered several recommendations, emphasizing the importance of fostering strategic awareness among leaders in government banks as a crucial element for successfully realizing long-term strategic objectives.